Clinical findings and results of diagnostic imaging in 82 dogs with gastrointestinal ulceration. (April 2017) - Fitzgerald, E.; Barfield, D.; Lee, K. C. L.; Lamb, C. R.
Abstract : Objectives: To describe clinical and imaging findings in dogs with confirmed gastrointestinal ulceration, to compare findings in dogs with perforated and non‐perforated ulcers and to estimate the sensitivities of radiography, ultrasonography and computed tomography (CT) for gastrointestinal ulceration and perforation. Methods: Retrospective review of medical records of 82 dogs that had a macroscopic ulcer in the gastric or intestinal mucosa diagnosed directly at endoscopy, surgery or necropsy and had survey radiography, ultrasonography or a CT scan of the abdomen during the same period of hospitalisation. Results: The most frequent clinical signs were vomiting in 88% dogs, haematemesis in 32%, melaena in 31% and weight loss in 7%. The most frequent imaging findings in dogs with non‐perforated ulcers were gastrointestinal mural lesion in 56%, mucosal defect compatible with an ulcer in 44% and peritoneal fluid in 21%. In dogs with perforated ulcers the most frequent imaging findings were peritoneal fluid in 83%, gastrointestinal mural lesion in 48%, peritoneal gas in 31% and mucosal defect compatible with an ulcer in 29%. Sensitivities of radiography, ultrasonography and CT were 30, 65 and 67% in dogs with non‐perforated ulcers and 79, 86 and 93% in dogs with perforated ulcers, respectively. Clinical Significance: In dogs with non‐perforated ulcers, survey radiography was usually negative whereas ultrasonography and CT frequently enabled detection of the site of the ulcer; in dogs with perforated ulcers, radiography was frequently positive for peritoneal gas and CT was a sensitive modality for both the ulcer and signs of perforation.